2011
DOI: 10.1037/a0025008
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and progesterone modify the effects of the serotonin reuptake transporter polymorphism on serotonergic responsivity to citalopram.

Abstract: Individual vulnerability to psychopathologies is linked to a number of genetic polymorphisms including the serotonin transporter (5HTT) promoter polymorphic region (5HTTLPR). A single copy of the short variant (s-variant) allele of 5HTTLPR confers increased susceptibility to anxiety disorders and depression and decreased efficacy of serotonin-releasing agents in pharmacotherapy compared to the homozygous long 5HTTLPR variant (l/l). The data suggesting that the 5HTTLPR polymorphism modulates the efficacy of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…Similar results have been found in primates, as the short allele of the 5-HTTLPR gene increased the neuroendocrine response to separation stress in infant macaques (Barr et al 2004), increased sensitivity to social stress in adult rhesus monkeys (Jarrell et al 2008), and was also associated with a decreased hormonal response to acute administration of the SSRI citalopram (Michopoulos et al 2011). These results suggest that polymorphisms of the 5-HTTLPR gene may have similar effects on stress sensitivity and antidepressant responsiveness in humans and non-human primates.…”
Section: Genetic Factorssupporting
confidence: 77%
“…Similar results have been found in primates, as the short allele of the 5-HTTLPR gene increased the neuroendocrine response to separation stress in infant macaques (Barr et al 2004), increased sensitivity to social stress in adult rhesus monkeys (Jarrell et al 2008), and was also associated with a decreased hormonal response to acute administration of the SSRI citalopram (Michopoulos et al 2011). These results suggest that polymorphisms of the 5-HTTLPR gene may have similar effects on stress sensitivity and antidepressant responsiveness in humans and non-human primates.…”
Section: Genetic Factorssupporting
confidence: 77%
“…This convention has been used by us and others to assess dominance status effects on a number of outcome measures in captive macaques (Kaplan et al, 1995; Kaplan et al, 1984; Kaplan et al, 2010; Kaplan and Manuck, 2008; Kaplan et al, 1982; Kaplan et al, 2002; Michopoulos et al, 2009; Michopoulos et al, 2011a; Michopoulos et al, 2010; Paiardini et al, 2009; Shively and Kaplan, 1984; Shively, 1998; Shively and Clarkson, 1994; Shively et al, 1997a; Shively et al, 1997b). The total number of subjects classified in this fashion was 16 dominant and 24 subordinate females.…”
Section: Methodsmentioning
confidence: 99%
“…Both estradiol and progesterone have been reported to inhibit the ability of the fluvoxamine to decrease the clearance of 5-HT (Benmansour et al 2009). Interestingly, Michopoulos et al (2011) reported an association with 5-HTTLPR and ovarian steroids considering antidepressant administration: increase in serum prolactin, a surrogate measure of serotonin activity, following citalopram administration was larger in LL than in S-variant females over the course of 2 h during concurrent estradiol and progesterone hormone replacement only in ovariectomized female rhesus monkeys, so ovarian function and the 5-HTTLPR polymorphism seem to interact to gate serotonergic reactivity in females.…”
Section: Discussionmentioning
confidence: 94%